Clostridium difficile toxins or infection induce upregulation of adenosine receptors and IL-6 with early pro-inflammatory and late anti-inflammatory pattern - Foschetti,D.A. (2020)
Clostridium difficile causes intestinal inflammation, which increases adenosine. We compared the expression of adenosine receptors (AR) subtypes A1, A2A, A2B, and A3 in HCT-8, IEC-6 cells, and isolated intestinal epithelial cells, challenged or not with Clostridium difficile toxin A and B (TcdA and TcdB) or infection (CDI). In HCT-8, TcdB induced an early A2BR expression at 6 h and a late A2AR expression at 6 and 24 h. In addition, both TcdA and TcdB increased IL-6 expression at all time-points (peak at 6 h) and PSB603, an A2BR antagonist, decreased IL-6 expression and production. In isolated cecum epithelial cells, TcdA induced an early expression of A2BR at 2s and 6 h, followed by a late expression of A2AR at 6 and 24 h and of A1R at 24 h. In CDI, A2AR and A2BR expressions were increased at day 3, but not at day 7. ARs play a role in regulating inflammation during CDI by inducing an early pro-inflammatory and a late anti-inflammatory response. The timing of interventions with AR antagonist or agonists may be of relevance in treatment of CDI.